Zeta study of water samples on Ba and Dong Nai river basins - Minh, Nguyen Trung; Hung, Doan Dinh; Thang, Cu Sy; Duc, Tran Minh (Vietnam Journal of Earth Sciences, 2015)
Findings zeta potential in river water samples of Ba and Dong Nai basin in Tay Nguyen area indicated that the properties of colloidal systems in the basin of Ba and Dong Nai river in Tay Nguyen region was relatively stable. The colloidal system was heavily influenced by the pH of the water, not by suspended component. The study also showed the influence of pH value on zeta potential values ​​in river water samples. For the three river water samples, pH values ​​tend to be inversely proportional to the zeta potential. Meanwhile, it is only true for the water samples taken in the middle section and the downstream of Dong Nai river basin, but upstream tended to be directly proportional. In addition, zeta potential in water samples at the regional hydroelectric plant located on 2 river basins, especially water sampled before and after the dams were also studied. The obtained results showed that affects of pH index on the zeta potential values ​​are completely correct and were a good agreement with discovered rules.ReferencesLại Huy Anh và nnk, 2004: Nghiên cứu cấu trúc địa hình, địa mạo, địa động lực lưu vực sông Ba và sông Côn. Báo cáo chuyên đề Viện Địa lý, Hà Nội. Đỗ Đức Dũng, Nguyễn Vũ Huy, 2012: Báo cáo tình hình quản lí lưu vực sông Đồng Nai 2011, Đỗ Tiến Lanh, 2010: Báo cáo đề tài KC08 18/06-10 “Quản lý tổng hợp lưu vực và sử dụng hợp lí tài nguyên nước lưu vực hệ thống sông Đồng Nai”. Lưu trữ tại viện Khoa học Thủy lợi miền Nam. Ngô Đình Tuấn và nnk, 2007: Quản lý tổng hợp tài nguyên nước lưu vực sông Ba, Trường Đại học Thủy lợi, Hà Nội. Nguyễn Viết Phổ, 1999: Tìm hiểu sông Đồng Nai. Hội nghị khoa học, công nghệ và môi trường miền Đông Nam Bộ họp tại Đà Lạt 12/1999, http://dalat.gov.vn Nguyễn Viết Phổ, 2003: Tài nguyên nước Việt Nam, Nhà xuất bản Nông Nghiệp, trang 137-152. Tran Hong Thai, Tran Thi Van, 2011: Assessment of climate change impacts on salinity intrusion in Hong-Thai Binh and Dong Nai river basins, VNU Journal of Science, Earth Sciences 27, 54-61. Zeta Meter 4.0 Instructor, Zeta-Meter Inc., PO Box 3008, Staunton  VA  24402  USA. 2009. Cổng thông tin quan tắc môi trường, Lưu vực sông Đồng Nai, http://www.cem.gov.vn, 01/03/2011.